Mastering Malware Analysis : the Complete Malware Analyst's Guide to Combating Malicious Software, APT, Cybercrime, and IoT Attacks. - Kleymenov, Alexey (Packt Publishing, Limited, 2019)
Malware analysis is a powerful investigation technique widely used in various security areas including digital forensics and incident response processes. Working through practical examples, you'll be able to analyze any type of malware you may encounter within the modern world.